Antiviral effects of the constituents derived from Chinese herb medicines on infectious bursal disease virus. (September 2013) - Sun, Yaogui; Song, Meiqin; Niu, Li; Bai, Xiyun; Sun, Na; Zhao, Xin; Jiang, Junbing; He, Junping; Li, Hongquan
Abstract Context: The prevalence of infectious bursal disease has brought about enormous financial losses to the world poultry industry. Chinese herb medicines can provide valuable materials for discovery and development of new drugs. Objective: To screen constituents derived from Chinese herb medicines for their antiviral activity against infectious bursal disease virus (IBDV) in vitro. Materials and methods: Twenty constituents derived from Chinese herb medicines and B87 strain of IBDV were used. The 50% cytotoxic concentration (CC50) and 50% effective concentration (EC50) were determined by visualization of cytopathologic effect (CPE) and 3-(4, 5-dimethyithiazol-2-yl)-2, 5-diphenyltetrazoliumbromide (MTT) test on chicken embryo fibroblast. Selectivity index (SI) and inhibition ratio (%I) were calculated from the data obtained from the MTT test. Results: Antiviral assays showed dipotassium glycyrrhizinate and ligustrazine hydrochloride among the 20 constituents tested exhibited significant inhibitory activity against IBDV in a dose-dependent manner. EC50 of dipotassium glycyrrhizinate and ligustrazine hydrochloride were 663.2 ± 268.4 and 92.52 ± 21.13 µg/mL, and SI were >4.52 and >21.62, respectively. The time-of-addition and virucidal assay indicated that anti-IBDV activity of the two constituents could be due to their inhibiting virus replication and/or inactivating virus directly. The inhibition of virus attachment was not observed in the adsorption inhibition assay. Dipotassium glycyrrhizinate and ligustrazine hydrochloride exhibited more than 70% and 80% inhibition of IBDV, respectively, at the maximum safe concentration. Discussion and conclusion: We believe that dipotassium glycyrrhizinate and ligustrazine hydrochloride can be used to develop a new anti-IBDV compound, and it is worth applying the constituents in clinical practice.